Directed Asymmetric Nickel‐Catalyzed Reductive 1, 2‐Diarylation of Electronically Unactivated Alkenes. (17th February 2023) - Dong, Zhan; Tang, Qiongyao; Xu, Changyu; Chen, Li; Ji, Haiting; Zhou, Sitian; Song, Liangliang; Chen, Liang‐An
Abstract: Transition‐metal catalyzed intermolecular 1, 2‐diarylation of electronically unactivated alkenes has emerged as an extensive research topic in organic synthesis. However, most examples are mainly limited to terminal alkenes. Furthermore, transition‐metal catalyzed asymmetric 1, 2‐diarylation of unactivated alkenes still remains unsolved and is a formidable challenge. Herein, we describe a highly efficient directed nickel‐catalyzed reductive 1, 2‐diarylation of unactivated internal alkenes with high diastereoselectivities. More importantly, our further effort towards enantioselective 1, 2‐diarylation of the unactivated terminal and challenging internal alkenes is achieved, furnishing various polyarylalkanes featuring benzylic stereocenters in high yields and with good to high enantioselectivities and high diastereoselectivities. Interestingly, the generation of cationic Ni‐catalyst by adding alkali metal fluoride is the key to increased efficiency of this enantioselective reaction. Abstract : A highly diastereoselective Ni‐catalyzed reductive 1, 2‐diarylation of unactivated internal alkenes was developed. Additionally, the enantioselective variant with unactivated terminal and challenging internal alkenes was also achieved, delivering various polyarylalkanes bearing benzylic stereocenters with good to high enantioselectivities and excellent diastereoselectivities.